A Survey about Protective Effect of Echinococcus Granulosus Protoscolices Surface Antigens in Preventing Secondary Hydatid Cyst - H Yousofi; M Hashemzadeh; K Kohansal; N Zabardast; H Shirzad; G Shahabi (Armaghane Danesh Bimonthly Journal, 2006)
ABSTRACT: